Development of Virtual Laboratory-Based of Learning to Improve Physics Learning Outcomes of High School Students - Abdjul, T; Ntobuo, N E; Payu, C (Jurnal Pendidikan Fisika Indonesia, 2019)
This study aims to develop virtual laboratory-based learning in physics subjects to improve the learning outcomes of high school students. This research is a research development with a 4-D model (define, design, develop, and dissemination). The results showed that the learning tools developed were categorized very well based on expert validation. Practical learning tools are used with an average value for the implementation of the learning process categorized very well and the average response of students to virtual laboratory based learning is very good. Student learning activities increased significantly after participating in learning. This research produces a valid, practical and effective learning tool by utilizing virtual laboratory media to improve student learning outcomes.